Pollution emissions and economic growth in Asia through the lens of the Environmental Kuznets Curve - Ponce, Brian Jason H.; Garcia, Yolanda T.; Carnaje, Gideon P.; Cuevas, Agham C. (2022)
The nonlinear relationship of pollution emissions with economic growth alongside energy consumption variables was examined to test the Environmental Kuznets Curve (EKC) hypothesis using a panel sample comprising 34 Asian economies from 2001 to 2013. Panel Autoregressive Distributed Lag models in the forms of Pooled Mean Group and Mean Group models were estimated and tested against one another using the Hausman test. For robustness checks, the same econometric techniques were applied to disaggregated panel groups based on income classifications. The study reveals that, while the EKC hypothesis holds in Asia, the findings were not robust across the disaggregated panel groups. The turning point in the Asian EKC was estimated to range from USD 32,003 to USD 38,793 per capita. The findings support the argument that the majority of Asian economies are yet to reach the ideal phase where economic growth decouples with environmental degradation.
Keywords: Pollution; Emission control; Economic development -- Asia